2022
DOI: 10.1186/s11671-022-03742-z
|View full text |Cite
|
Sign up to set email alerts
|

Visual Cu2+ Detection of Gold-Nanoparticle Probes and its Employment for Cu2+ Tracing in Circuit System

Abstract: Highly sensitive, simple and reliable colorimetric probe for Cu2+-ion detection was visualized with the L-cysteine functionalized gold nanoparticle (LS-AuNP) probes. The pronounced sensing of Cu2+ with high selectivity was rapidly featured with obvious colour change that enabled to visually sense Cu2+ ions by naked eyes. By employing systemic investigations on crystallinities, elemental compositions, microstructures, surface features, light absorbance, zeta potentials and chemical states of LS-AuNP probes, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…It is found that good reliability and repeatability of CQD@AuNP 2-based colorimetric probes are validated. In addition, sensing performances were compared with other reported designs, 15,34–43 where the present work indeed demonstrated a remarkable improvement in viewing LOD criteria, covering a wide detectable range and pH environmental tolerance, as indicated in Table 1. This benefited practical employment for instant, visual and reliable Cu 2+ sensing.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…It is found that good reliability and repeatability of CQD@AuNP 2-based colorimetric probes are validated. In addition, sensing performances were compared with other reported designs, 15,34–43 where the present work indeed demonstrated a remarkable improvement in viewing LOD criteria, covering a wide detectable range and pH environmental tolerance, as indicated in Table 1. This benefited practical employment for instant, visual and reliable Cu 2+ sensing.…”
Section: Resultsmentioning
confidence: 65%
“…Accordingly, the reduction of covalently bonded thiol groups that bridged the CQDs and AuNP cores was accompanied by the oxidation of Cu 2+ ions, which was exploited as the key for the morphological transition from aggregated state to dispersed feature, as evidenced in the literature 15 and Fig. S2(b) (ESI†).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations